The Effectiveness of Rational Emotive Behavior (REB) Group Counseling in Reducing Fear of Missing Out (FOMO) Among Stusents of SMK PGRI 2 MALANG: Keefektifan Konseling Kelompok Rational Emotive Behavior (REB) Untuk Menurunkan Fear of Missing out (FOMO) Pada Siswa SMK PGRI 2 MALANG - Putri, Eke Rena Setia Poppy Billa Adawiyah (INSIGHT: Jurnal Bimbingan Konseling, 2024)
Fear of Missing Out (FoMO) is one of the phenomena that is prevalent among students. FoMO has a lot of impact on many aspects of students' lives. The research is dedicated to investigating the effectiveness of Rational Emotive Behavior Group Counseling in reducing Fear of Missing Out among students of SMK PGRI 2 MALANG. This study is experimental research with a One-Group Pretest-Posttest design. The collection of data technique was conducted using the FoMO Scale developed by Kaloeti, consisting of 12 items. For data analysis, a non-parametric statistical method, the Wilcoxon Matched-Pairs Signed Test, was used. The research subjects were 5 students from SMK PGRI 2 Malang who had a high average level of Fear of Missing Out and were willing to participate in REB group counseling. The Wilcoxon test statistics showed a Z value of -2.023 and an Asymp. Sig. (2-tailed) value of 0.043, which is less than 0.05 (< 0.05), indicating a difference between the pretest and post-test results in students' Fear of Missing Out levels. This research demonstrates that REB group counseling is effective in reducing the level of FoMO among vocational high school students.